NEUROGENE-GENETIC FACTORS AND MECHANISMS DEVELOPMENT OF ULCER DISEASE - Иванов, Леонид Николаевич; Колотилова, Марина Леонидовна (Medicine in Kuzbass, 2020)
Purpose of the study – to develop an improved author’s theory of the etiology of the pathogenesis of peptic ulcer. Materials and methods. In order to develop the author’s views on the etiology and pathogenesis of peptic ulcer treated with about 40 different publications and analyzed the results of their own research. Results. Therefore, genetic theory of neurogenic etiology and pathogenesis of gastric ulcer and duodenal ulcer 12 highly optimized explain causal relationships ulcer patient, allowing variations in the prevalence or otherwise of neurosis factor or local genetic factors. However, obviously other things that only a combination of neurogenic factor genetically altered reactivity of the gastroduodenal system (the presence of the target organ) causes chronic ulcers. Developed-tannaya our theory of peptic ulcer disease, a disease related to psychosomatic pathology allows to develop effective therapies including drugs with psihokorregiruyuschim action.